1983
DOI: 10.1111/j.1346-8138.1983.tb01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Nail Candidiasis

Abstract: Onychomycosis caused by Candida is often accompanied by paronychia. Not only the morbid changes in the nailplate caused by the true parasitism by Candida but also the secondary changes in the nail due to candidial paronychia are sometimes handled as though they were candidial onychia. Onychomycosis caused by candidial infection, i.e., nail candidiasis, is entirely different in its pathogenetic respects from the secondary ungual changes due to candidial paronychia. The reason why both are classified together as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…12 The reason for the higher frequency of fungal infection of fingernails among women is probably because of the frequent immersion of the hands in water (associated with working in wet environment as housewives) or exposure to chemicals and trauma. 8,13 Although previous reports have indicated that dermatophytes are responsible for most of the nail infections, 3 we found that onychomycosis caused by yeast was the most common clinical form with C. albicans isolated in 71.4% of cases. This species has been frequently found in onychia and paronychia by yeast.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…12 The reason for the higher frequency of fungal infection of fingernails among women is probably because of the frequent immersion of the hands in water (associated with working in wet environment as housewives) or exposure to chemicals and trauma. 8,13 Although previous reports have indicated that dermatophytes are responsible for most of the nail infections, 3 we found that onychomycosis caused by yeast was the most common clinical form with C. albicans isolated in 71.4% of cases. This species has been frequently found in onychia and paronychia by yeast.…”
Section: Discussionmentioning
confidence: 56%
“…The increased prevalence of onychomycosis in the toenails in men could be the result of more traumas in the nails because of occlusive footwear, which favours the appearance of disease 12 . The reason for the higher frequency of fungal infection of fingernails among women is probably because of the frequent immersion of the hands in water (associated with working in wet environment as housewives) or exposure to chemicals and trauma 8,13 …”
Section: Discussionmentioning
confidence: 99%
“…However, others have reported no notable difference, 8 while some investigators found fungal infection of fingernails to be more common in men than women 10 . The reason for the greater frequency of fungal infection of fingernails among women is probably due to the frequent immersion of the hands in water or exposure to chemicals and trauma 11 . In addition, women are more concerned about the appearance of their fingernails than men.…”
Section: Discussionmentioning
confidence: 99%
“…The traumatic aetiology of the dystrophy must be pointed out. The role of dystrophy of the nail in relation with systemic disease such as systemic lupus erythematous has been previously stressed [11] as well as the role of diabetes mellitus and chronic administration of corticosteroids. Cushing's syndrome and Raynaud's disease were also considered as risk factors [2].…”
Section: Discussionmentioning
confidence: 99%
“…The aetiological responsibility of C. parapsilosis in mixed infections is questionable, as in a study including 39 healthy subjects, C. parapsilosis was isolated in 51.3% of the cases [11], indicating that this fungus was one of the main species of the microflora of the subungual space. It is very likely that in most cases, C. parapsilosis colonizes the surface of nails invaded by another Candida species responsible for the clinical event.…”
Section: Discussionmentioning
confidence: 99%